Outer membrane protein C (OMPC) epitope of Shigella flexneri 3a as a potential marker of primary immunodeficiencies (PID) and isolated anti-OmpC antibodies as a tool for immunoglobulin replacement therapy - Naporowski, Piotr; Witkowska, Danuta; Rybka, Jacek; Pawlak, Edyta; Lewandowicz-Uszyńska, Aleksandra; Masłowska, Ewa; Gamian, Andrzej (Frontiers in Immunology, 2025)
IntroductionOver 6 million people worldwide are affected by primary immunodeficiencies (PIDs), which often remain undiagnosed, and the diagnostic process is complex and challenging. Dysfunction of the immune system can lead to permanent damage to body systems and organs; moreover, Ig replacement therapy carries the risk of anaphylactic shock following the administration of the immunoglobulin preparation. The present study proposes an alternative testing method for IgA deficiency, using the BSA-peptide conjugate with the RYDERY sequence, which may serve as a simpler alternative to complex diagnostic schemes. MethodsWe analysed the levels of anti-OmpC S. flexneri 3a antibodies in sera from healthy individuals (40 samples from children and 66 samples from adult blood donors) and patients (127 samples from patients with PID, 83 samples from patients with RRTI), utilising the native bacterial OmpC protein and two BSA-peptide conjugates: one linear and one with a cyclic structure.ResultsThe obtained results showed that for OmpC and both conjugates, IgA titres – unlike IgG – were significantly lower in patients with PID and RRTI compared to healthy controls. Additionally, the levels of specific IgA antibodies differed significantly between men and women in both the PID patient and healthy adult groups when using native OmpC protein, but not when employing conjugates as the antigen. These findings strongly support using the conjugate, particularly with the linear peptide, instead of the whole OmpC protein in immunochemical assays. The level of IgA in patients’ sera is generally lower compared to that of healthy controls and decreases with age when conjugates are used for analysis. In the mouse model, specific, isolated anti-OmpC antibodies from both human and mouse serum had similar protective activity against Shigella infection. DiscussionThe results demonstrate that the additional use of the cyclic/linear peptide-BSA conjugate offers a significant advantage over the use of the complete OmpC protein for immunological testing in PID diagnostics. Furthermore, specific anti-OmpC antibodies may be beneficial in the complementary therapy for patients with PIDS.